Laporan Baru Tentang Dacus longicornis dan Dacus petioliforma (Diptera:Tephritidae) di Daerah IstimewaYogyakarta = Newly Reported: Dacus longicornis and Dacus petioliforma (Diptera:Tephritidae) in Jogjakarta Special ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak. Filsafat UGM, 2004)
Research was conducted in Jogjakarta from April to October 2004, to know the existence and description of Dacus spp. in Indonesia especially in Jogjakarta Special Province. The result of the exploration shows that there are two species of Dacus spp. attracted to cue lure traps. The species are Dacus (Callantra) longicornis and Dacus (Callantra) petioliforma with characteristics as follows: notopleuron and mesopleural stripe are brownish on a longicomis and yellow on D. petioliforma